Ethical Leadership Scale: Adaptation into Indonesian and Evaluation of Internal Structure Using GSCAM - Manara, Muhammad Untung; Arlianto, Arlianto; Ridho, Ali (Indonesian Psychological Research, 2026)
This study aims to adapt and validate the Ethical Leadership Scale (ELS) into Indonesian to provide a reliable score and valid interpretation for measuring ethical leadership in Indonesian organizational contexts. The adaptation process involved forward translation, synthesis, expert panel review, and pre-testing. Validity evidence was supported by Aiken’s V index with inputs from organizational psychology experts. Data were collected from Indonesian participants and analyzed using generalized structured component analysis with measurement errors incorporated (GSCAM) and reliability estimates, including Omega coefficients. Invariance investigation across demographic variables was also conducted. The Indonesian version of the ELS demonstrated strong content evidence (Aiken’s V ≥ 0.80) and excellent internal consistency (ω = 0.920), fulfilling model fit indices. Measurement invariance analysis confirmed that the adapted scale was equivalent across gender, education level, marital status, and job position, indicating its robustness in diverse groups. The findings indicate that the Indonesian version of the ELS is a psychometrically sound and culturally appropriate tool for assessing ethical leadership. This instrument offers theoretical and practical contributions, enabling researchers and practitioners to examine and promote ethical leadership in Indonesian organizational settings.